Using participatory learning and action to empower women’s groups to improve feeding practices in Madhya Pradesh - Kanani, Shubhada; Singh, Rachna; Baqar, Syed; Mahajan, Uma; Belwal, L.M. (International Food Policy Research Institute, 2015)
Participatory learning and action (PLA) is a promising approach to promote infant and young children feeding (IYCF) and other health, nutrition, water sanitation, and hygiene (HNWASH) practices. Since February 2014, PLA has been implemented in 14 blocks in eight districts of Madhya Pradesh through the Sanjhi Sehat program, which is led by the Government of Madhya Pradesh’s State Rural Livelihood Mission (SLRM). The mission implements Sanjhi Sehat in five districts, and district- level nongovernmental organizations (NGOs) implement it in three additional districts. Technical assistance is provided by the Madhya Pradesh Technical Assistance and Support Team (MPTAST) under the Department for International Development (DIFD)-supported Madhya Pradesh Health Systems Reforms program. Other partners include the Department of Health and Family Welfare and the Department of Women & Child Development, whose staff ensure that all services of the program are accessible and accountable to the community. The Public Health Engineering Department is responsible for the safe water and sanitation (toilet construction) infrastructure and services, which forms an important component of the HNWASH interventions.